Peningkatan Kedisiplinan Belajar Siswa melalui Reward and Punishment pada Pembelajaran Dasar Kuliner Kelas X Wirausaha - Anandita R Indarwan; Nunung Nurjanah; Yetti Setyorini (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
The research was motivated by the low level of student learning discipline, which was demonstrated through behaviors such as using mobile phones during learning, eating in class, lack of learning readiness, and low focus on teacher explanations. This study aims to determine: 1) the application of rewards and punishments in improving student learning discipline in the Culinary Basics Subject in class X Culinary Entrepreneurship; 2) student learning readiness and focus at the beginning of learning through the application of reward and punishment methods at SMK Negeri 3 Malang. This study used the Classroom Action Research (CAR) model of Kemmis and McTaggart which consisted of planning, action implementation, observation, and reflection stages. The study was conducted in two cycles with 35 students as subjects. Data collection techniques were carried out through observation and documentation, while data analysis used quantitative descriptive. The results showed that the application of reward and punishment methods was able to significantly improve student learning discipline. In cycle I, the percentage of student learning discipline reached 57.1% with a poor category. After corrective actions were carried out in cycle II, the percentage increased to 91.4% with a very good category. This improvement is evident in changes in student behavior, who have become more focused, orderly, responsible, and more compliant with class rules during the learning process. Thus, the implementation of rewards and punishments has proven effective in improving learning discipline and creating a more conducive learning environment in culinary vocational courses.